Targeting Neuronal Populations of the Striatum - Durieux, Pierre F.; Schiffmann, Serge N.; de Kerchove d'Exaerde, Alban (Frontiers in Neuroanatomy, 2011)
The striatum is critically involved in motor and motivational functions. The dorsal striatum, caudate–putamen, is primarily implicated in motor control and the learning of habits and skills, whereas the ventral striatum, the nucleus accumbens, is essential for motivation and drug reinforcement. The GABA medium-sized spiny neurons (MSNs, about 95% of striatal neurons), which are targets of the cerebral cortex and the midbrain dopaminergic neurons, form two pathways. The dopamine D1 receptor-positive (D1R) striatonigral MSNs project to the medial globus pallidus and substantia nigra pars reticulata (direct pathway) and co-express D1R and substance P, whereas dopamine D2 receptor-positive (D2R) striatopallidal MSNs project to the lateral globus pallidus (indirect pathway) and co-express D2R, adenosine A2A receptor (A2AR) and enkephalin (Enk). The specific role of the two efferent pathways in motor and motivational control remained poorly understood until recently. Indeed, D1R striatonigral and D2R striatopallidal neurons, are intermingled and morphologically indistinguishable, and, hence, cannot be functionally dissociated with techniques such as chemical lesions or surgery. In view of the still debated respective functions of projection D2R striatopallidal and D1R striatonigral neurons and striatal interneurons, both in motor control and learning but also in more cognitive processes such as motivation, the present review sum up the development of new models and techniques (bacterial artificial chromosome transgenesis, optogenetic, viral transgenesis) allowing the selective targeting of these striatal neuronal populations in adult animal brain to understand their specific roles.